Manual for training of extension workers farmers - R. BRAGA ...[et al] (FAO, 2001)
This manual offers IPM training for the replacement of MeBr as a soil fumigant; it briefly describes the elements and steps of this training process and gives the framework for its realization. It includes a useful bibliographical and indicates Web page related to MeBr and new alternatives.